β-Arrestin-1 is required for adaptive β-cell mass expansion during obesity - Luiz F. Barella (Nature Portfolio, 2021)
During insulin-resistance, the compensatory expansion of beta-cell mass is able to delay or the onset of overt type 2 diabetes. Here, the authors report that beta-arrestin-1, an intracellular protein known to regulate signalling through G protein-coupled receptors, is essential for beta-cell replication and function in insulin-resistant mice.